Photogenerated Electron Transfer Process in Heterojunctions: In Situ Irradiation XPS - Zhang, Peng; Li, Yukun; Zhang, Yongshang; Hou, Ruohan; Zhang, Xilai; Xue, Chao; Wang, Shaobin; Zhu, Bicheng; Li, Neng; Shao, Guosheng (Small methods, 2020)
Photoelectron transfer between heterojuctions is an important process for photocatalysis, and identification of the electron transfer process provides valuable information for catalyst design. Herein, Ti3C2, one of the widely used two‐dimensional materials, is used to produce a heterojunction of TiO2 and Ti3C2 by an in situ growth method and the photogenerated electrons transfer between the two components for photocatalytic water splitting to hydrogen is investigated. Theoretical simulation and experimental tests proclaim that electrons transfer from Ti3C2 to TiO2 forms an internal electric field, which implies that there exists the driving force of electronic movement from TiO2 to Ti3C2. In situ irradiation X‐ray photoelectron spectroscopy shows the binding energies of TiC (in Ti3C2) and TiO (in TiO2) move toward negative and positive positions, respectively, verifying the photogenerated electrons produced from TiO2 and transferring to Ti3C2 driven by the internal electric field. In addition, the amount of TiO2 nanoparticles also affects the hydrogen evolution rate. Several parallel experiments are designed to uncover the fact that less or excess amount of TiO2 nanoparticles leads to a tinier shift of binding energy, which hints the quantity of heterojunction is a considerable factor in photocatalytic performance. This work develops a new method to directly monitor the photoelectron transfer process between heterojuctions. An in situ irradiation X‐ray photoelectron spectroscopy coupled with UV light optical fiber measurement setup is developed to monitor the photoelectron transfer process between heterojuctions.